How policewomen's experiences of 'male construct' interact with sustainability of career development and promotion practices : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, New Zealand - Mace, Stephanie Jane (Massey University, 2019)
Women in today’s New Zealand Police organisation work across almost all roles and ranks, including 14 percent representation at commissioned and non-commissioned officer level. Disparities relating to women and men’s access to senior and high-level roles and workgroups continue to challenge police, despite new policy and performance initiatives for cultural reform. Understanding how policewomen’s experiences of police as a gendered organisation interact with sustainability of career development and promotion practices exposes the rules of formation that permit the conditions and outcomes of structural processes and practices that engender women in police as they negotiate their career progression strategies. 28 policewomen at commissioned and non-commissioned officer ranks were interviewed in a semi-structured conversational style about their experiences. A Foucauldian discourse analysis was applied, attending to the gendered social power relations that define and delimit social practice and the governance of women, both within and outside the workplace. The analysis showed that dominant heteronormative discourses regulate policewomen’s practices of gender coherence within a hegemonic socio-cultural discourse of masculinist rationalisation that differentiates male / female, masculine /feminine as contingent subject positions and investments in compliance and/or resistance to social institutions of work and family. Furthermore, women were positioned within and through discourse as neoliberal active gendering agents whose subjection to, and mastery of, masculinist ideals for leadership shape career progression as the strategic navigation of work and family commitments in accordance with a duplicitous and inegalitarian system. Alternate realities were also presented as reproducing and re-producing masculine values and the gender order for progression in the police hierarchy. This research contributes to the paucity of scholarship attending to the career progression experiences of senior-ranking policewomen in a gendered organisation that function to reproduce dominant discourses as social power relations that intervene in the practices of women and men in police. It may also provide understanding for what may be required to transform and/or vanquish relations of power in order to effect meaningful long-term organisational transformation.
Keywords: New Zealand Police; Policewomen; Police administration; New Zealand; Police; Attitudes; Sex discrimination against women; Career development